Coordination of SPS and CES to Mitigate Oscillatory Condition on Power Systems - Rahmat Septian Wijanarko; Herlambang Setiadi; Teguh Aryo Nugroho (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
Oscillatory condition on power system (low-frequency oscillation) is one of the important factors to determine the quality of the power system. With the increasing number of load demand, this condition is getting worse in recent years. Hence, utilizing addition devices to maintain and mitigate the oscillatory condition of power system is crucial. This paper proposed a method to mitigate power system oscillation by installing one of the flexible AC transmission system (FACTS) devices called solid phase shifter (SPS) and energy storage devices called capacitor energy storage (CES). To analyze the performance of power system with SPS and CES, the eigenvalue and damping ratio analysis are used. Time domain simulation is also investigated to analyze the dynamic behaviors of power system considering SPS and CES. Furthermore, increasing number of load demand is carried out to analyze how much load can be increased without increasing power to the grid. From the simulation, it is found that SPS and CES can mitigate low-frequency oscillation on power system indicated by highest damping, smallest overshoot, and fastest settling time. It is also found that load demand can be increased significantly when SPS and CES installed to the system.